Free Tissue Transfer in Sickle Cell Disease: A Case Report and Systematic Review - Huang, Anne; Patel, Ronak A.; Gottlieb, Lawrence J. (Archives of Plastic Surgery, 2023)
Hemoglobinopathies such as sickle cell disease (SCD) are traditionally considered a relative contraindication to free tissue transfer, due to concerns that erythrocyte sickling will increase the risk of microvascular thrombosis and flap failure. This article describes a case report with the successful use of free tissue transfer in a patient with SCD and provides a systematic literature review on free tissue transfer in SCD. A retrospective chart review was performed of a patient with SCD who underwent free tissue transfer at the authors' institution. A systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was performed using the keywords “free tissue transfer,” “free flap,” or “microsurgery” and “sickle cell” on PubMed, Ovid/Medline, and Scopus. A 29-year-old male with delayed presentation of an electrical burn to the face and scalp underwent wound closure with a free anterolateral thigh flap. Key management principles included red blood cell transfusion to keep hemoglobin S under 30% and hemoglobin greater than 10 g/dL, maintenance of hydration, normothermia, adequate analgesia, and postoperative anticoagulation. Systematic literature review identified 7 articles describing 13 cases of free tissue transfer in 10 patients with SCD, with combined complete free flap success in 10 of the 13 flaps. Free tissue transfer can be successfully performed in patients with SCD. However, evidence on the optimal management of this unique patient population in the perioperative period after free tissue transfer is limited to case reports in the literature.
Keywords: free tissue transfer; free flap reconstruction; microsurgery; sickle cell disease